New Perspectives in Biblical and Rabbinic Hebrew - Hornkohl, Aaron D.; Khan, Geoffrey (Cambridge Semitic Languages and Cultures, 2021)
"Most of the papers in this volume originated as presentations at the conference Biblical Hebrew and Rabbinic Hebrew: New Perspectives in Philology and Linguistics, which was held at the University of Cambridge, 8-10th July, 2019. The aim of the conference was to build bridges between various strands of research in the field of Hebrew language studies that rarely meet, namely philologists working on Biblical Hebrew, philologists working on Rabbinic Hebrew and theoretical linguists. This volume is the published outcome of this initiative. It contains peer-reviewed papers in the fields of Biblical and Rabbinic Hebrew that advance the field by the philological investigation of primary sources and the application of cutting-edge linguistic theory. These include contributions by established scholars and by students and early career researchers. "